Optimizing employee efforts: The implications of job design for administrative staff performance in higher education - Salifu, Inusah; P.K Mantey, Philip; Kwadwo Worlanyo, Emile (Journal of Interdisciplinary Studies in Education, 2021)
This study examined the effects of job designs on administrative staff performance in higher education. It further sought to establish whether selected demographic characteristics of the administrators had any relationships with main job design effects on their individual performances in assigned roles. Four hundred and twenty participants drawn from the administrative sections of five universities in Ghana were purposively sampled. Data were analyzed using descriptive and inferential statistics. The study identified that job designs had many effects on administrative staff performance including being able to specialize in a particular task and to gain in-depth knowledge in task performance. The research also found significant associations between selected demographic characteristics of the staff and the key job design effects on staff performance.